Baby boomers' development of resources and strategies to engage as later life university students. Issue 5 (3rd September 2019) - Hardy, Margaret; Oprescu, Florin; Millear, Prudence; Summers, Mathew
ABSTRACT: To determine the resources baby boomers use or develop to strategise successful engagement as later life university students, informal semi-structured interviews were conducted with 12 Australian baby boomers. The phenomenological data was analysed, themes identified and aligned with the volition phase stages of the adapted Health Action Process Approach model. Interviewees displayed varying levels of self-efficacy and coping strategies. Having a sense of purpose and involvement in the social environment of a university appears to create positive functioning that can contribute to healthy ageing and well-being. The findings from this study could assist university administrators and policy makers to develop strategies to attract and support this niche sector of university students.